Tác động của COVID-19 đến giá cổ phiếu, lợi nhuận và hoạt động của ngân hàng thương mại Việt Nam - Nguyễn Hữu , Huân; Tô Trần Diễm , Quỳnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The study uses the random effects model to analyze the relationship between the COVID-19 pandemic’s impact on stock prices, profits and operations of Vietnamese commercial banks from a sample of data collected from March 2018 – March 2022. The results show that the COVID-19 pandemic has a positive impact on stock prices, profits and performance of banks. Besides, an interesting finding is that technology development at banks does not help them be more efficient during the COVID-19 pandemic but has a positive impact on bank profits during this period.